INGLIZ VA O’ZBEK TILLARIDA SIYOSIY TERMINLARNING TARJIMADAGI MUOMMOLARI (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
In this article, the lexical-semantic and spiritual features of the terms related to a certain field of the English language in the process of translation into the Uzbek language are studied. At the same time, the translator should be able to define and interpret the phonetic and grammatical features, meaning, essence and function of each word with the help of text and dictionary, and then to be able to choose a linguistic unit similar to it in his own language are discussed.